Application of Y-chromosomal microdeletions in a homicide case. (September 2020) - Yang, Xingyi; Liu, Hong; Liu, Changhui; Xu, Quyi; Yang, Dian; Han, XiaoLong; Chen, Ling; Lei, Bo; Liu, Chao; Du, Weian
Highlights: Y chromosomal microdeletions make and Y haplotype very rare. Y-STR microdeletions were found in the suspect and crime scene but not in the suspects' patrilineal. The potential use of Y-STR in inconclusive autosomal STR analysis cases. Abstract: A case study involving an intentional homicide case in November 2018, in which the autosomal genotypes of the suspect were unavailable and only part of deletions of Y-STR loci were identified by Y-chromosomal typing. The suspect, male, was charged with beating the decedent, female, over the head with an iron water pipe to death. The use of standard autosomal DNA profiling to identify the suspect was unattainable due to the extensive volume blood of the decedent on the murder weapon which was inevitably cleaned by running water at the crime scene. As a result, autosomal genotypes of the suspect were unavailable and only partial samples of deletions of Y-STR loci were identified by Y-chromosomal typing. Y-STR analysis (Yfiler™ plus and AGCU Y36) was used on the collected DNA extracts and compared to reference samples of the suspect, as well as his father and brother in an attempt to positively identify the suspect as the perpetrator of the murder. Subsequent Y-STR genotyping for the suspect, his father and brother indicated that Y-STR genotype of the suspect was consistent with that discovered on the physical evidence and the deleted Y-STR loci were identical for both. No deletions of Y-STR genotype were observed in the suspect's father and brother. After changing a Y-STR kit, the deleted loci were still present in the suspect. In Addition, sequencing of the whole Y-chromosomal genes was performed on the samples taken from the suspect and his father and brother. Segmental deletions at Yq 11.222-Yq 11.23 of the suspect were observed and the deleted Y-STR markers were right on the deleted Y-chromosomal segments. In this case, although the suspect could not be identified by the autosomal STR profiles detected on the physical evidence, the discovery of identical Y-STR genotype and the identical deletions of Y-chromosomal segments made it plausible that DNA on the murder weapon was left behind by the suspect. This case study shows that in criminal cases like this, where the autosomal STR evidence is unattainable, Y-STR evidence can be used effectively as a substitute to identify the suspect.